Enhancer of zeste 2 polycomb repressive complex 2 subunit polymorphisms in melanoma skin cancer risk. Issue 10 (7th September 2020) - Belpinati, Francesca; Malerba, Giovanni; Dal Toè, Melissa; Ceccuzzi, Laura; Rodolfo, Monica; Poli, Albino; Turco, Alberto; Vergani, Elisabetta; Sangalli, Antonella; Gomez‐Lira, Macarena
Abstract: Melanoma is the most deadly skin cancer, and its incidence is growing. EZH2, a member of the Polycomb Group (PcGs) proteins family, plays an important biological role in the occurrence and development of melanoma. EZH2 germline genetic polymorphisms have not been yet evaluated in melanoma predisposition. Three hundred thirty sporadic Italian melanoma patients and 333 healthy volunteers were genotyped to analyse the association between EZH2 variants rs6950683, rs2302427, rs3757441, rs2072408 and melanoma risk. The functionality of rs6950683 alleles was investigated in keratinocytes (HaCat), melanoma cells (A375) and human embryonic kidney cells (HEK293), using promoter‐reporter assays. Genotype distribution of SNPs showed that rs6950683T and rs3757441C alleles were positively associated with melanoma risk ( P = .003 and .004, respectively). Haplotype analysis revealed that TCCA and CCCG haplotypes were associated with a higher risk of melanoma ( P = .02 and .04, respectively). Functional assays demonstrated that allele rs6950683T reduce promoter activity in the three cell lines analysed compared to C allele. rs6950683T and rs3757441C alleles in the EZH2 gene appear positively associated with melanoma risk in the analysed population. In addition, we demonstrated for the first time the functional role of rs6950683 upstream polymorphism on EZH2 gene expression regulation.